Indicadores e determinantes clínicos e epidemiológicos de hanseníase em menores de quinze anos, Mato Grosso, Brasil - Freitas, Bruna Hinnah Borges Martins de (2015)
Objective: To analyze the indicators and the clinical and epidemiological determinants of leprosy in individuals under the age of fifteen registered in the Mato Grosso’s System for Notifiable Diseases, Brazil. Method: It is an epidemiological study developed in three steps that include: characterization of 2.455 new cases of leprosy in individuals under the age of fifteen notified between 2001 and 2013; identifying the historical tendency of epidemiological indicators of leprosy in this population by means of the Prais-Winsten procedure for analyzing generalized linear regression; and comparison of sociodemographic, clinical and epidemiological characteristics of 429 individuals notified with leprosy between the priority and non-priority cities, by using the chi-square test at a significance level of 5%, as well as the spatial distribution of these cities by means of the ArcGIS 10.2 software. Results: The first study indicated the average incidence of 22,7 cases per 100 thousand inhabitants in individuals under the age of fifteen. The greatest proportion of entry belonged to the male gender (51,6%; n=1268) and the age group from 10 to 14 years (65%, n=1595). Among the clinical characteristics, 67,3% (n=1.652) were classified as paucibacillary and 45,8% (n= 1.125) with a single injury. Regarding the detection mode, 46,2% (n=1.133) of entries were due to spontaneous demand. It was observed that 60,6% and 52,1% of the information about the accomplishment of skin smear in the diagnosis and presentation of reactive episode, respectively, were considered ignored and/or not completed. In the second study, it was found a decreasing tendency of the general coefficient of incidence, with an average annual rate of 5,5% (95% CI: -7,5 – -3,5) and increasing tendency with an growth of 6,7% (95% CI: 2,7 – 10,8) in the proportion of multibacillary cases, 9,4% (95% CI: 4,4 – 14,7) of cases diagnosed with borderline clinical form and 14,0% (95% CI: 7,9 – 20,4) of cases with physical disability level 2 at the time of diagnosis. There was an increasing tendency in the average proportion of examined contacts, with a growth of 4,1% (95% CI: 1,2 – 7,1), whilst the average proportion of healing in the period was considered poor (39,7% ), with stationary tendency. The last study identified that 73,9% (n=317) of the new cases were notified in priority cities. It was observed a difference in the proportion of cases registered among the cities, with a greater proportion in priority ones in relation to the age group from five to nine years (χ²=4,09; p=0,043), white color (χ²=7,01; p=0,008) and tuberculoid clinical form (χ²=3,89; p=0,048); and greater proportion in non-priority cases in relation to the non-urban area (χ²=24,23; p<0,001), two to five injuries (χ²=5,93; p=0,014) and spontaneous demand (χ²=6,16; p=0,013). Of the 141 assessed cities of the state according to the spatial distribution, 58,1% (n=82) showed a high, very high and hyper-endemic average coefficient of incidence, and, of these, 34,1% (n=28) include the group of priorities. Conclusion: The historical tendency of the average coefficient of incidence of leprosy in individuals under the age of fifteen proved to be decreasing in the period. Nonetheless, the clinical and epidemiological characteristics of the disease and the tendencies of epidemiological indicators have indicated the late diagnosis with a permanence of communicable sources. The majority of cases were registered in priority cities. However, both demonstrate the hyperendemicity of the diseases, thereby influencing with the answers of control of the epidemics in the state.